Lange's 1938 model: dynamics and the “optimum propensity to consume” - Assous, Michaël (2014)
Oskar Lange's 1938 article “The Rate of Interest and the Optimum Propensity to Consume” is usually associated with the original IS-LM approach of the late 1930s. However, Lange's article was not only an attempt to illuminate Keynes's main innovations but the first part of a wide project that included the development of a theory of economic evolution. This paper aims at showing that Lange's article can help in illuminating critical aspects of this project: in particular, Lange's idea that a synthesis between Kaldor's and Kalecki's theories and that of Schumpeter, might have been possible and that it represented (in intentions) a “modern” and consistent reconstruction of the Marxist theory of the business cycle. Section 2 clarifies Lange's early reflection on dynamics. Section 3 centres on Lange's 1938 static model and indicates the effects of a change of saving on investment. Section 4 suggests a dynamic reconstruction from which are addressed important arguments raised by Lange in a series of papers written between 1934 and 1942.